Terahertz metamaterial on-chip sensing platform for live cancer cell microenvironment analysis - Kim, Taeyeon; Kwak, Jisung; Roh, Yeeun; Sim, Sang Jun; Ryu, Yong-Sang; Song, Hyun Seok; Seo, Minah (Elsevier BV, 2025)
Sensitive and accurate cancer biomarker detection is highly demanded in biochemistry and medicine. In particular, lactic acid and the acidic extracellualr environment are crucial for the energy supply of cancer, immune evasion, and metastasis. One of the most used analytical techniques such as molecular-tag strategy provides molecular-scale resolution and robustness. However, the complexity of cancer necessitates multi-marker and labor-intensive analysis for determining oncogenesis. Here, we propose nanophotonic terahertz metamaterial-based on-chip technology offering high performance in precision for investigating the extent of aerobic glycolysis and cancer cell proliferation. Utilizing the nanoscale slot structure as a container located on optical hotspot, collective motions of lactic acid together with their intermolecular interactions against an acidic extracellular environment were monitored without perturbation using THz wave. Additionally, the sensing platform enables selective focusing on cellular types and acidic tumor microenvironment by implementing observation mode switching function through resonant frequency tuning characteristics and signal processing strategies. The terahertz metamaterial has been optimized in both its fabrication process and optical control properties, successfully achieving a small size of 6 mm square with scalability and nanoscale pattern features. This overcomes the high production costs that have been a hurdle in traditional metamaterial applications, while also enabling on-chip functionality. The THz-metamaterial sensing platform features comprehensive analysis of cancer biomarkers and related environmental changes, demonstrating its potential as a comprehensive cancer pathophysiology.